If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + -8x)(3 + -2x) = 0 Multiply (1 + -8x) * (3 + -2x) (1(3 + -2x) + -8x * (3 + -2x)) = 0 ((3 * 1 + -2x * 1) + -8x * (3 + -2x)) = 0 ((3 + -2x) + -8x * (3 + -2x)) = 0 (3 + -2x + (3 * -8x + -2x * -8x)) = 0 (3 + -2x + (-24x + 16x2)) = 0 Combine like terms: -2x + -24x = -26x (3 + -26x + 16x2) = 0 Solving 3 + -26x + 16x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -8x)(3 + -2x) = 0Subproblem 1
Set the factor '(1 + -8x)' equal to zero and attempt to solve: Simplifying 1 + -8x = 0 Solving 1 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -8x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -8x = 0 + -1 -8x = 0 + -1 Combine like terms: 0 + -1 = -1 -8x = -1 Divide each side by '-8'. x = 0.125 Simplifying x = 0.125Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Divide each side by '-2'. x = 1.5 Simplifying x = 1.5Solution
x = {0.125, 1.5}
| 5(x+8)=6(x-7) | | 4(2x+1)-3(x+3)=5(x-2) | | 2445/2200 | | 2x+3(x-2)-3(x-6)=0 | | 5x+5=3(5x-5)-20x | | 6-12x/4-7=14 | | 5x+130=8x+181 | | 5+2*10=n | | 10s/5=10 | | (2x-1)(2x-3)= | | (x-6)(2x+3)= | | X^5x=100 | | 5+2n=-5 | | 4x=(70-x) | | x+5(5x-1)=99 | | 10y+9-2y=4y+3y+12 | | x-.5x=1000 | | 6(7x-6)+8=-154 | | 2x-5=(x-5) | | (1.3_0.06)/0.8 | | -31=4w+1 | | 0=x^5+2x^3+x | | 7-6a=-5-3(a-5) | | N+28=2N+16 | | 12=3(v-6) | | 6-3w=12 | | 2x-7=15-5x | | 5x-3=8x-21 | | 12x+33=x | | 7(x-7)=-4-16 | | -6.3m+2.7m= | | 0.75x+37-2.75=3(4+x) |